Kajian Pelaksanaan Perbaikan Berkelanjutan Filosofi Kaizen pada Proyek Konstruksi di Indonesia - Putri, Kartika Nur Rahma (Department of Civil Engineering, Diponegoro University, 2020)
Kaizen as a quality management system offers a new approach to increase productivity by improving existing production processes without investing in new tools/procedures. This study aimed to determine the application of continuous improvement in construction projects according to kaizen philosophy. The research was conducted using descriptive analysis to describe the process of continuous improvement in a construction project. Data were collected using a questionnaire method on 24 building and road projects and interviews with two contractors. This study's results indicate that the application of the kaizen principle in construction projects is still limited. The research reveals that project planning has been carried out but not entirely following field conditions, standardization of work methods already exists but not detailed, all parties in the project have been involved in the construction process, but initiatives to make improvements have not been seen because it is still focused on corrective evaluation and work completion. The challenges in implementing continuous improvement are the lack of a quality management system, lack of working time, lack of consistency in the implementation of quality, and lack of worker’s skill in carrying out work. Some improvements required to support continuous improvement are to encourage top management's role in the application of quality management systems and internalization of the kaizen principle to all workers. The involvement of all production elements in maintaining product's quality in the internal system also needs to be improved.